Rainfall, Financial Development, and Remittances : Evidence From Sub-Saharan Africa - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2011)
We use annual variation in rainfall to examine the effects that exogenous, transitory income shocks have on remittances in a panel of 42 Sub-Saharan African countries during the period 1960-2007. Our main finding is that these income shocks have a significant positive effect on remittances, but that the effect is significantly decreasing in the share of domestic credit to GDP. So much so, that at high levels of credit to GDP transitory increases in income had a significant negative effect on remittances. Our findings are consistent with the view that remittances take advantage of unexploited domestic investment opportunities that can exist due to domestic credit market frictions. Our findings also support the view that when barriers to financial flows are low, remittances effectively provide insurance against transitory income shocks.